Evaluation of Serum Leptin Level in Psoriasis Patients and its Relation with the Severity of Disease - Mohammad Reza Sobhan; Mohammad Jamshidi; Hamid Reza Ghasemibasir; Elham Khanlarzadeh (پزشکی بالینی ابن سینا, 2023)
Background and Objective: The association of leptin with psoriasis is currently controversial. The purpose of this study was to evaluate serum leptin levels in patients with psoriasis and its relationship with the severity of the disease. Materials and Methods: In this case-control study, serum leptin levels were measured in 40 patients with psoriasis and 40 age- and gender-matched healthy controls by sandwich enzyme-linked immunosorbent assay method. The severity of psoriasis was assessed by the Psoriasis Area and Severity Index (PASI). Data were analyzed using SPSS software version 16. Results: Of 40 patients, 35 (87.5%) had plaque psoriasis, 3 (7.5%) had palmo-plantar, and one of the remaining two patients had erythrodermic psoriasis while the other one had a pustular type. The mean disease severity based on PASI was 10.2 with a range of 0.8 to 39.9. The most common sites of involvement were generalized (27.5%), upper and lower extremities together (20.0%), lower extremities alone (15%), and trunk and lower extremities (15%) in descending order. Leptin was higher in the patient group than the control group (19.2±16.3 ng/ml versus 15.5±16.1 ng/ml) (P=0.227). The correlation between leptin and body mass index was positive and significant in both groups. No significant relationship was found between the severity and duration of disease and leptin. Conclusion: The findings of this study showed that similar to most studies, serum leptin levels were higher in patients with psoriasis than in healthy subjects, and in obese people, this difference was greater than in normal-weight individuals